A New Insight into the Role of CART in Cocaine Reward: Involvement of CaMKII and Inhibitory G-Protein Coupled Receptor Signaling - Yu, ChengPeng; Zhou, XiaoYan; Fu, Qiang; Peng, QingHua; Oh, Ki-Wan; Hu, ZhenZhen (Frontiers in Cellular Neuroscience, 2017)
Cocaine- and amphetamine-regulated transcript (CART) peptides are neuropeptides that are expressed in brain regions associated with reward, such as the nucleus accumbens (NAc), and play a role in cocaine reward. Injection of CART into the NAc can inhibit the behavioral effects of cocaine, and injecting CART into the ventral tegmental area (VTA) reduces cocaine-seeking behavior. However, the exact mechanism of these effects is not clear. Recent research has demonstrated that Ca2+/calmodulin-dependent protein kinase II (CaMKII) and inhibitory G-protein coupled receptor signaling are involved in the mechanism of the effect of CART on cocaine reward. Hence, we review the role of CaMKII and inhibitory G-protein coupled receptor signaling in the effect of CART on cocaine reward and provide a new insight into the mechanism of that effect. In this paper, we will first review the biological function of CART and discuss the role of CART in cocaine reward. Then, we will focus on the role of CaMKII and inhibitory G-protein coupled receptor signaling in cocaine reward. Furthermore, we will discuss how CaMKII and inhibitory G-protein coupled receptor signaling are involved in the mechanistic action of CART in cocaine reward. Finally, we will provide our opinions regarding the future directions of research on the role of CaMKII and inhibitory G-protein coupled receptor signaling in the effect of CART on cocaine reward.